Zmiany cen na rynku zbóż po przystąpieniu Polski do Unii Europejskiej - Rusielik, Robert (Changes of Grain Prices on the Grain Market after Poland's Accession to the EU, 2005)
The EU system of intervention and price regulation on the grain market started in Poland on 1st May 2004. In consequence the grain prices in the period between 1st November and 31 May are determined by the EU regulations and they depend on EUR/PLN exchange rate. This situation will continue to exist until Poland joins the Euro zone.The main purpose of the research is to demonstrate differences in changes of grain prices depending on the currency applied. The research covers 2003-2004 time period. The results showed in the research form the part of broader research program.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 250-253